BOPHY Derivatives as Phototherapeutic Agents for the Photodynamic Inactivation of Microorganisms - Chávez Hernández, Claudia (2024)
Photodynamic inactivation (PDI) of microorganisms is a promising antimicrobial therapy to fight against multiple-resistant microbial pathogens. The optimization of this therapy depends on developing novel photosensitizers (PS). In this sense, three BOPHY derivatives (BP, BP-Br and BP-I) were synthetized, studied, and compared to assess their antimicrobial photodynamic properties. BP is a promising fluorescent probe for cell imaging, while the halogenated analogs (BP-Br and BP-I) are excellent oxygen photosensitizing agents. BP-Br presented an adequate balance between ROS production and emission properties. The photokilling action and the binding to bacterial cells of BOPHYs were evaluated in vitro against methicillin-resistant Staphylococcus aureus(MRSA) and Escherichia coli (resistant to β-lactam antibiotics) bacteria. Our results demonstrated that the halogenated BOPHY derivatives were effective PS in inactivating MRSA. The antimicrobial action sensitized by these PS was potentiated by adding KI. The combination of halogenated BOPHY and KI led to a complete elimination of both Gram-positive and Gram-negative bacteria. To the best of our knowledge, this is the first time that BOPHY derivatives have been applied to photokill pathogenic microorganisms. This work establishes the groundwork for the development of new BOPHY-based PS with potential applications in the field of PDI.